Beauty’s Betrayal: Mycobacterium abscessus Case Series Following Aesthetic Procedures in the Brazilian Amazon - Carbonell, Roberto C. C.; Oliveira, Letícia L. F.; Galan, Luis E. B.; Filardi, Eloise T. M. [UNESP]; Lins, Alysson B. M.; Nattrodt, Jânio J. M.; Dantas, Domingos S. M.; Bernardi, Adilson C. A.; Cerni, Felipe A.; Pucca, Manuela B. [UNESP] (MDPI, 2024)
The Brazilian market holds the second position globally in the beauty sector, poised to surpass the USD 50 billion mark in the upcoming years. Aesthetic procedures encompass a spectrum, ranging from non-invasive ones, such as drainage, radiofrequency, ultrasound, and cryolipolysis, to more invasive techniques, including fillers, botulinum toxin, microneedling, micropigmentation, carboxytherapy, and enzyme application. This wide array of treatments has yielded satisfactory cosmetic results for individuals who opt out of surgical procedures. However, despite being categorized as having low complexity, they still carry inherent risks. These risks are often exacerbated by the breach of the skin barrier, the exposure of organs and spaces, or the presence of implantable devices. Among the bacteria most isolated concerning this matter are non-tuberculous Mycobacteria. This study presents descriptive case reports involving three patients under the care of the Infectious Diseases Department at General Hospital of Roraima (HGR). These patients were diagnosed with Mycobacterium abscessus infections subsequent to undergoing enzyme application procedures. Although these cases involve the same microorganism, they exhibit varying degrees of severity, ranging from the development of locally nodular formations to a progression towards sepsis. These cases provide an opportunity to delve into the diagnostic subtleties and clinical implications of these infections while also prompting a critical evaluation of therapeutic strategies. Additionally, the report underscores the potential risks associated with routine aesthetic procedures.
Keywords: aesthetic procedures; cosmetic; enzyme application; infections; mesotherapy; non-tuberculous Mycobacteria